Effect of Sowing Dates and Compound Fertilizer NPK on Growth and Yield of Flax (Linum usitatissimum L.) - Rayan F. A. Al-Obady; Ayad T. Shaker (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2022)
Two field experiments were conducted during winter growing season 2019-2020 at Ninevah Governorate at two locations: Talkief and Al-Hamdaniya. The main objective was to study the effect of two sowing dates (November 2017 and December 2017), and four levels of N15P15K15 fertilizers (0, 100, 150 and 200 kg. ha-1) on growth and yield of flax under rainfed conditions. The factorial experiment was carried out in Randomized Complete Block Design (R.C.B.D.) with triplicate. The results showed that there were significant differences (p<0.05) between sowing dates in all the studied characters in the both locations, the date of sowing (November 17) gave the highest rate of plant height, number of fruiting branches. plant-1, number of capsules. plant-1, number of seeds. capsule-1, 1000 seed weight , seed yield, seed oil percentage and linolenic acid percentage. Adding NPK fertilizer with 200 Kg NPK.ha-1 to the soil was superior in some characters i.e. plant height, number of fruiting branches. plant-1, number of capsules. plant-1 and number of seeds. capsule-1 in Al-Hamdaniya location, Whereas linolenic acid percentage was superior in Talkief location, Also highest seeds oil percentage was obtained in both locations. The interaction between date (November 17) with 200 kg.ha-1 of N15P15K15 fertilizer was significantly (p<0.05) superior in linolenic acid percentage in Talkief location only.